Pathomechanisms of bone loss in rheumatoid arthritis - Sakthiswary, Rajalingham; Uma Veshaaliini, Rajeswaran; Chin, Kok-Yong; Das, Srijit; Sirasanagandla, Srinivasa Rao (Frontiers in Medicine, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease, in which the inflammatory processes involve the skeletal system and there is marked destruction of the bones and the surrounding structures. In this review, we discuss the current concepts of osteoimmunology in RA, which represent the molecular crosstalk between the immune and skeletal systems, resulting in the disruption of bone remodeling. Bone loss in RA can be focal or generalised, leading to secondary osteoporosis. We have summarised the recent studies of bone loss in RA, which focused on the molecular aspects, such as cytokines, autoantibodies, receptor activator of nuclear kappa-β ligand (RANKL) and osteoprotegerin (OPG). Apart from the above molecules, the role of aryl hydrocarbon receptor (Ahr), which is a potential key mediator in this process through the generation of the Th17 cells, is discussed. Hence, this review highlights the key insights into molecular mechanisms of bone loss in RA.